Revisiting social intelligence development in islamic secondary education: A sociological analysis of students in private madrasah aliyahin pekanbaru city - Marianti Kahar; Ilyas Husti; Zamsiswaya (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Amid the growing complexity of social interaction in contemporary education, concerns have intensified regarding the inadequacy of cognitive-centered approaches in preparing students for real-world interpersonal demands. This study fundamentally redefines the development of social intelligence by examining how it is socially constructed within Islamic secondary education through the dynamic interaction of teacher roles and school environments. Employing a qualitative multiple-case study design across three private Madrasah Aliyah, the research integrates semi-structured interviews, non-participant observations, and document analysis to capture nuanced interactional processes and lived experiences. The findings reveal that social intelligence does not emerge as an individual attribute but as an emergent, relational competence produced through structured and sustained social engagement embedded within pedagogical and institutional systems. Teachers act as critical agents who not only facilitate interaction but actively shape its quality through modeling, scaffolding, and feedback, while the school environment functions as an enabling structure that amplifies or constrains participation. Crucially, the study demonstrates that optimal development occurs only when these elements operate in synergy, forming a coherent and iterative social learning ecosystem. By challenging dominant outcome-based models of Social Emotional Learning, this research advances a process-oriented and system-based conceptualization of social intelligence as context-dependent and dynamically constructed. The study contributes theoretically by integrating sociocultural and educational perspectives into a unified analytical framework, and practically by offering actionable insights for designing context-sensitive interventions in faith-based institutions. Ultimately, this research positions social intelligence as a central pillar of holistic education and provides a globally relevant framework for its sustainable development in increasingly complex social environments